Usage and Impact of the Internet for Appalachian Chambers of Commerce - James R. Lindner (Journal of Applied Communications, 1999)
The use of various Internet applications has opened the door for businesses in isolated areas to participate in a global economy. But has this new tool penetrated Appalachia Ohio, and can Extension help community and economic development professionals better use the Internet to achieve greater success? Chambers of Commerce throughout rural America are important stakeholders and clientele of Extension. A study using a descriptive survey method assessed the perceptions of Chamber of Commerce Executive Directors in Appalachia Ohio regarding the Internet. The study found relatively few significant barriers that limit access to the Internet and that proficiency in basic Internet skills is associated with higher perceived job success factors.